Municipal transfer systems: Regional effects of public activity - Jan Monnesland (European Regional Science Association (ERSA), 2001)
While the regional incentive programmes attract high attention in the regional policy debate, less attention is devoted towards the municipal transfer systems. Nevertheless, these systems will in many countries redistribute more financial resources between regions than the more narrowly defined regional policy programmes. The municipal transfer programmes are described briefly for the 5 Nordic countries. Focus is made on the volume of the programmes (relatively to the size of the local government activity level) as well as on the principles adopted for shaping the transfer programmes. The material shows a great variation between the countries, both in philosophy as well as in practical implementation. The systems are normally based on two pillars, one intending to equalise differences in local income potentials, and one to compensate for differences in the needs for public services. The last pillar will be based on models giving credit to social and demographic factors generating the need structure. The analyses focus on differences between the countries in how demographic and social factors are weighted when the need structure is calculated, and how these differences lead to different regional effects of the transfer programmes. The paper also focus on how differences in the equalising of the income potentials lead to different regional effects. The paper end up in a description on the total "un-intended" regional distribution effect of the programmes. The un-intended aspect refer to the fact that regional policy is not (at least formally) an argument in the programmes, they are designed from a welfare and income distribution perspective. However, some aspects are included for some of the countries with a declared regional policy aim. Also, regional policy strategies are often referred to in the debate on the programmes, even when they are not formally included. The mix between implicit and explicit regional policy elements is discussed on a comparative perspective.
Keywords: 330